Land use and livelihood: A research based on thirukkural - Subajini, U. (University of Jaffna, 2015)
Thirukkural, composed two thousand year ago by the divine port Thiruvalluvar and renowned as the world's common book of ethics, has a store of information pertaining to a number of matters. This work contains one thousand and one hundred and thirty stanzas which include various topics such as politics, sociology, economics, geography, culture, environmental factors and the life styles of people. Thiruvalluvar has clearly portrayed the life styles of the people who lived in the society of his time. This article aims at bringing out the place assigned to land use and livelihood as revealed in Thirukkural. This is a discussive study based on secondary data. A number of literacy reviews have also been made in relation to this research. Under land use, Thiruvalluvar has highlighted agriculture factors, while under the topic livelihood, he deals with fishing, afforestrastration and livestock rearing. It is worth noticing that the facts pointed out by Thiruvalluvar apply even to today's modern era. This article should serve as a guide to future researches on this subject.
Keywords: Land use; Livelihood; Thiruvalluvar; Thirukkural